FORMULASI DAN UJI STABILITAS FISIK GEL HAND SANITIZER KOMBINASI EKSTRAK DAUN SIRIH HIJAU (PIPER BETLE) DAN EKSTRAK DAUN KELOR (MORINGA OLEIFERA) SEBAGAI ANTIMIKROBA - Anggraini, Herlina (Politeknik Tiara Bunda, 2022)
Antiseptics or handsanitizers generally contain alcohol and triclosan which when used continuously can irritate the skin, causing a burning sensation on the skin. One alternative to reduce the chemical content in handsanitizers is to use natural ingredients that contain antimicrobial compounds. Natural ingredients used in this study are betel leaf extract and Moringa leaf. The purpose of this study was to determine the right combination of betel and moringa leaf extract concentrations for a handsanitizer formulation with good physical stability and antimicrobial activity. This research method used a completely randomized design (CRD) with a combination of concentrations, namely FI (25% betel leaf extract and 75% moringa leaf extract), F2 (50% betel leaf extract and 50% moringa leaf extract) and F3 (75% betel leaf extract and 25% Moringa leaves). The results showed that green betel leaf and moringa leaf extracts can be made as hand sanitizer gel preparations with various combinations of concentrations. Hand sanitizer gel of green betel leaf and moringa leaf extract with a concentration of 75% betel leaf extract and 25% moringa leaf extract had the best physical properties and stability